A metalinguistic semantics for echo questions - Sudo, Yasutada (Proceedings of the Amsterdam Colloquium, 2007)
This paper proposes a compositional semantics for echo questions in the structured meanings approach to questions, claiming that they are metalinguistic questions about expressions. It also points out inadequacies of the focus semantic approach of Artstein 2002 and the non-metalinguistic approach of Ginzburg and Sag 2001.